What does it take to sell environmental policy? An empirical analysis of referendum data - Daniel Halbheer; Sarah Niggli; Armin Schmutzler (University of Zurich, Socioeconomic Institute, 2005)
We analyze the factors that influence the support for environmental policy proposals. Swiss referendum data show that proposals obtain more yes-votes if they do not restrict consumption possibilities directly, if they are endorsed by the largest business association, if environmental preferences are strong and economic conditions are favorable at the time of the referendum. Also, there are more pro-environmental votes in cantons with higher population density. On the other hand, yes-votes do not seem to depend on whether a proposal involves a tax or not.
Keywords: P16; Q28; 330; direct democracy; environmental policy; public choice; referendum; Umweltpolitik; Neue politische Ökonomie; Demokratie; Schätzung; Schweiz